PENGEMBANGAN MEDIA CORONG HITUNG UNTUK MENINGKATKAN KETERAMPILAN BERHITUNG TENTANG OPERASI BILANGAN PADA SISWA KELAS I SEKOLAH DASAR - noer, pratiwi rosita; anggit, prabowo (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2019)
Development of Funnel Counting media is very necessary because there is no learning media that can help students learn about number operations. This condition has an impact on students' numeracy skills which are still low. To overcome this problem there needs to be an appropriate solution. One of them is by developing media that attract students in the form of a Calculating Funnel media. This study aims to determine the steps for developing and the feasibility of media Counting Funnels. This research is research and development (R & D) with the development model of 4D (Four-D), namely Define, Design, Development, Disseminate. The subject of this study was the first grade students of SD Muhammadiyah Bleber with a total of 18 students. The instruments of data collection are questionnaires, interview guides, tests, and documents. The data analysis technique used is qualitative analysis and quantitative analysis. The results of validation research media experts get a value of 93.75 (Very Good), validation of material experts get 85.41 (Very Good), validation of learning experts get 85.41 (Very Good), the results of expert validation get comments and suggestions as a reference for doing product revision. The results of a small group trial with 8 students scored 87.50 (very good). The teacher's assessment received a score of 94.11 (very good). Student responses got a value of 95.83 (very good). While the usage trial with 18 students got a value of 86.50 (very good). The teacher's response to the use trial received a score of 97.50 (very good). students' responses get a score of 97.50 (very good). Overall, from the Funnel Counting media validation test, it is feasible to use it in grade 1 elementary mathematics learning.